Determining factors associated with breastfeeding and complementary feeding practices in rural Southern Benin. Issue 1 (6th November 2020) - Bodjrènou, Fifali Sam Ulrich; Amoussa Hounkpatin, Waliou; Termote, Céline; Dato, Geoffroy; Savy, Mathilde
Abstract: This study aimed at characterizing breastfeeding and complementary feeding practices in a food‐insecure area of Benin and identifying factors associated with these practices. A cross‐sectional study was conducted in the districts of Bopa and Houéyogbé among n  = 360 mother–child pairs. Children aged 0–17 months were considered. Socioeconomic characteristics among children and mothers, Breastfeeding on demand, Breastfeeding frequency during children illness, and Positioning and Attachment of children while breastfeeding were assessed using semi‐structured interviews and observations. Qualitative 24‐hr recalls were administered to mothers to compute WHO recommended complementary feeding practices indicators namely minimum dietary diversity (MDD), minimum meal frequency (MMF), and minimum acceptable diet (MAD) among 6–17 months old children ( n  = 232). Associations between each feeding practice and mothers' socioeconomic characteristics were tested using multivariate generalized linear models. Breastfeeding on demand and good positioning and attachment for breastfeeding rates were 59% and 66%, respectively. Only 26% of mothers used to increase breastfeeding frequency when their children were ill. The proportions of children who met MDD, MMF, and MAD were 51%, 75%, and 44%, respectively. Children living in Houéyogbé were less likely to be breastfed on demand compared with those living in Bopa ; however, they had better breastfeeding frequency during illness and meal frequency. Socioeconomic factors with significant association with breastfeeding practices were children age and sex and mothers' education, ethnicity, and employment status. Complementary feeding practices were positively associated with children's age but not with other socioeconomic characteristics. Breastfeeding and complementary feeding practices were almost suboptimal or medium and still need to be improved through well designed nutrition intervention program including nutrition education. Abstract : In the present study, we evaluated breastfeeding and complementary feeding practices among children aged, respectively, 0–17 months and 6–17 months in a rural and food‐insecure area in Southern‐Benin, West Africa. We determined also socioeconomic and agricultural factors, which were associated to these practices in order to well design a nutrition education program. This graph presents the percentages of children who have achieved recommended breastfeeding and complementary feeding practices in the rural districts of Bopa and Houeyogbe (Southern Benin).